Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

beans3

  • 3 years ago

–2(y – 3) = 2y – 6 whats y?

  • This Question is Closed
  1. Rosy95
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    distribute -2 to get... -2y+6=2y-6 then put like terms together 6=4y-6 12=4y divide 4 from both sides to get your answer 12/4=y y=3

  2. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy